A low‐profile and wideband circularly polarized patch antenna using four resonance modes. Issue 3 (25th November 2021) - Liang, Chang‐Feng; Lyu, Yun‐Peng; Chen, Dong; Cheng, Chong‐Hu
Abstract: In this paper, a low‐profile and wideband circularly polarized patch antenna using four resonance modes is presented. It is one kind of four‐port antenna implemented by loading five shorting pins on the circular patch. In order to achieve wideband properties, TM11 and TM22 modes are stimulated in circular patch, along with their polarization orthogonal modes (TM11+ and TM22+ modes). The TM11+ mode is excited by the Γ‐shaped feed, while the TM22 mode and TM22+ mode is stimulated by four shorting pins in close proximity to the Γ‐shaped feed. Due to the strong coupling between shorting pins and Γ‐shaped feed, the peak electric field generated on the two opposing shorting pins causes the magnetic current density on the circumference of the patch to be changed, which in turn leads to the realization of broadside radiation in the TM22 and TM22+ modes. In addition, the function of the shorting pin loaded in the center of the patch is to improve the impedance matching when TM22 and TM22+ modes are operated. Cooperated with the devised one‐to‐four feed network with equal amplitude and progressive phase difference of 90°, the wideband circularly polarized patch antenna is obtained. To verify this design concept, a prototype is fabricated and measured. The diameter of the patch is 0.68 λ 0 and the profile is 0.078 λ 0 ( λ 0 is the wavelength in the free space at the center frequency). The measured relative bandwidth of VSWR < 2 is 106%, involving 1.53–4.96 GHz, while that of AR < 3 dB is 98%, ranging from 1.54 to 4.48 GHz. Besides, the measured LHCP gain > 3 dBic in the frequency band of 1.48–4.42 GHz.